Zola and the Gorgons: Cheese and Gossip in Le Ventre De Paris - Sayers, William (Petits Propos Culinaires, 2012)
This article explores the olfactory sensations evoked by passages in Zola’s novel based on the huge indoor food market, Le Ventre de Paris (The Belly of Paris, 1873).